It's Time for Medical Schools to Introduce Climate Change Into Their Curricula. (December 2018) - Wellbery, Caroline; Sheffield, Perry; Timmireddy, Kavya; Sarfaty, Mona; Teherani, Arianne; Fallar, Robert
Abstract : Climate change presents unprecedented health risks and demands universal attention to address them. Multiple intergovernmental organizations, health associations, and health professions schools have recognized the specific importance of preparing physicians to address the health impacts of climate change. However, medical school curricula have not kept pace with this urgent need for targeted training. The authors describe the rationale for inclusion of climate change in medical education and some potential pathways for incorporating this broad topic into physician training and continuing medical education. Reasons include the magnitude and reach of this transboundary issue, the shared responsibility of the U.S. health care sector as a major contributor to greenhouse gas emissions, and the disproportionate effects of climate change on vulnerable populations. The integration of climate-change-related topics with training of essential physician skills in a rapidly changing environment is feasible because many health topic areas already exist in medical school curricula in which climate change education can be incorporated. To fully integrate the health topics, underlying concepts, and the needed clinical and system-wide translations, content could be included across the scope of training and into continuing medical education and faculty development. The authors provide examples of such an approach to curricular inclusion.